Pengaruh Atribut Kemasan dan Kualitas Produk Halal Terhadap Keputusan Pembelian - Khairul Anshor Nst; Salman Nasution (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
This study aims to determine the effect of packaging attributes and quality of halal products on purchasing decisions for cake at Nurul Bakery Stores. This study uses a qualitative research method with an associative approach. The analysis used is descriptive analysis to determine the influence between the independent variable and the dependent variable. The research findings show that the test results (F), Fcount is 9.435 FTable 3.49, this means Ho is rejected, meaning that simultaneously there is no positive and significant effect of the independent variable on the dependent variable. The probability value (Sig.) is 0.002<0.05, indicating that the effect of the independent variable simultaneously is not significant on the dependent variable. However, the results of the (-t) test, show that partial packaging attribute variables have a positive and significant effect on purchasing decisions for cake products at Nurul Bakery Shops and product quality variables have a positive and significant effect on purchasing decisions for cake products at Nurul Bakery Shops. R Square of 0.526 means 52.6% of purchasing decision factors can be explained by the attributes of packaging and product quality. While 47.4% can be explained by factors not examined in this study such as Price, Promotion, and Lifestyle.